Synthesis of an efficient heteroatom-doped carbon electro-catalyst for oxygen reduction reaction by pyrolysis of protein-rich pulse flour cooked with SiO2 nanoparticles - Gokhale, Rohan; Unni, SreeKuttan M.; Puthusseri, Dhanya; Kurungot, Sreekumar; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Development of a highly durable, fuel-tolerant, metal-free electro-catalyst for oxygen reduction reaction (ORR) is essential for robust and cost-effective Anion Exchange Membrane Fuel Cells (AEMFCs). Herein, we report the development of a nitrogen-doped (N-doped) hierarchically porous carbon-based efficient ORR electrocatalyst from protein-rich pulses. The process involves 3D silica nanoparticle templating of the pulse flour(s) followed by their double pyrolysis. The detailed experiments are performed on gram flour (derived from chickpeas) without any in situ/ex situ addition of dopants. The N-doped porous carbon thus generated shows remarkable electrocatalytic activity towards ORR in the alkaline medium. The oxygen reduction on this material follows the desired 4-electron transfer mechanism involving the direct reduction pathway. Additionally, the synthesized carbon catalyst also exhibits good electrochemical stability and fuel tolerance. The results are also obtained and compared with the case of soybean flour having higher nitrogen content to highlight the significance of different parameters in the ORR catalyst performance.